Biology and ecomorphology of stream fishes from the rio Mogi-Guaçu basin, Southeastern Brazil - Katiane M. Ferreira (Neotropical Ichthyology)
The córrego Paulicéia is a direct tributary of the rio Mogi-Guaçu, located in Santa Rita do Passa Quatro, State of São Paulo, Southeastern Brazil. This stream runs inside a savannah-like (cerrado) environment and it associated vegetation. Biological and ecomorphological aspects of its fish community were studied in three stretches of the stream, denominated herein as the upper, middle and lower courses. The fish fauna recorded in this study consisted of 15 species, belonging to five orders and nine families, based in a total of 715 collected individuals representing 1,450 kg of biomass. The most important abiotic factors related to the occurrence and distribution of the fish fauna were the substrate, current speed, and presence or absence of riparian vegetation. The analysis of 336 stomach contents of 13 species demonstrated that 65% of food items are autochthonous, 32% allochthonous, and 3% are of unknown origin. Four alimentary guilds could be identified, based on the predominant food items: omnivores with tendency to insectivory - Astyanax paranae, A. fasciatus and Piabina argentea; larvivores - Corydoras difluviatilis, Cetopsorhamdia iheringi, Phenacorhamdia tenebrosa, Characidium gomesi, Eigenmannia virescens, and Rhamdia quelen; periphyton feeders - Hisonotus sp., Hypostomus ancistroides and Synbranchus marmoratus; and piscivore - Hoplias malabaricus. Reproductions data are presented for Astyanax altiparanae and Hisontus sp. Three ecomorphological groups could be established, based on swimming, feeding, and microhabitat strategies: nektonic (A. fasciatus, A. paranae, Bryconamericus stramineus, P. argentea, H. malabaricus and Phallotorynus jucundus), benthic (C. gomesi, P. tenebrosa, C. iheringi, R. quelen, C. difluviatilis, H. ancistroides and Hisonotus sp.), and necktobenthic (E. virescens and S. marmoratus).